The Resistance of Denti-Geogrid Reinforcement in a Sand Model Based on the Pullout Test - Wei, Fang; Jingsheng, Zhang; Lijun, Shi; Xudong, Zha (Frontiers in Materials, 2021)
Aim at investigating the pullout resistance of the Horizontal-Vertical reinforcement, “denti-geogrid” was assembled by bonding “denti-strip” with the geogrid and the pullout tests were carried out. Subsequently, the analytical approaches were investigated to calculate the pullout resistance on the basis of the surface sliding model, Perterson & Anderson’s model, Jewell’s model, Chai’s model, as well as the proposed stress summation model. Moreover, a new index named “scale factor” was suggested to reflect the proportion of bearing resistance provided by transversal members. The research showed that: (1) under the same test conditions, the pullout resistance of denti-geogrid was much higher than that of common geogrid. All common geogrids showed linear strain softening in the later stage of pullout tests. Given the same normal stresses, due to the expansion of effective areas suffering lateral earth pressure, more denti-strips meant more significant resistance. (2) Among five theoretical approaches, the solutions of the proposed stress summation model made the best agreement with lab test results, with an average relative error of 2.82%. On the other hand, the stress summation model also showed a simplicity in calculation. (3) Due to higher gradient of the fitting curve of scale factors, the bearing resistance’s ratio under lower normal stress would be increasing faster, which means the lateral resistance of denti-strips could play a more decisive role in cases of low stress level.